Track cycling: An analytical model - Lukes, R.; Carre, M.; Haake, S. (The Engineering of Sport 6, Volume 1 Developments for Sports, 2006)
This paper presents an analytical model of track cycling the purpose of which is to provide a tool that allows subtle changes to be made to the bike, rider or environment and a corresponding change in Performance realised. The model has been derived specifically for track cycling, and considers the implications of riding in a velodrome. Various inputs are required by the model, such as; rider power, atmospheric conditions, tyre properties, velodrome geometry, aerodynamic properties and bike and rider characteristics. A fundamental principle of the model is that the centre of mass travels a shorter distance in the bends than the wheels. An application is demonstrated by examining Chris Boardman`s 4 km individual pursuit world record ride. The predicted completion time shows excellent agreement with the record, however assumptions regarding atmospheric conditions and equipment dictate that further Validation is necessary. Examining the Output demonstrates three fundamental principles of track cycling; (1) aerodynamic resistance is highly dominant, (2) the bike accelerates in the bends and decelerates in the straights and (3) the rolling resistance increases in the bends. A graphical-user-interface is to be produced for the model providing coaches and researchers with an accessible and practical investigative tool.